Recurrence of Helicobacter pylori Infection in Bolivian Children and Adults After a Population‐Based "Screen and Treat" Strategy. Issue 5 (16th May 2014) - Sivapalasingam, Sumathi; Rajasingham, Anu; Macy, Jonathan T.; Friedman, Cindy R.; Hoekstra, Robert M.; Ayers, Tracy; Gold, Benjamin; Quick, Robert E.
Abstract Background Strategies to prevent gastric cancer by decreasing Helicobacter pylori infections in high‐prevalence, low‐income countries could include a population‐based "screen and treat" eradication program. Methods We tested residents of two rural villages for H. pylori infection using urea breath test (UBT), treated infected persons using directly observed therapy (DOT), retested for cure, and retested after 1 year later for H. pylori infection. Findings We tested 1, 065 (92%) of 1153 residents from two villages in rural Bolivia. Baseline H. pylori prevalence was 80% (95% confidence interval [CI]: 78–84). Age‐specific cure rates were similar (≥92%) after DOT. Among those cured, 12% (95% CI: 8–15) had recurrent infection. Age‐specific annual H. pylori recurrence rates for combined villages were 20% (95% CI: 10–29) in persons <5 years, 20% (95% CI: 10–29) in 5–9 years, 8% (95% CI: 1–15) in 10–14 years, and 8% (95% CI: 4–12) in persons ≥15 years. Compared with the referent population, those ≥15 years, recurrent infections were significantly more likely in children <5 years (odds ratios [OR] 2.7, 95% CI: 1.2–5.8) and 5–9 years (OR 2.7, 95% CI: 1.4–5.1). Interpretation Children <10 years had high H. pylori recurrence rates following a population‐based screen and treat program; this H. pylori eradication strategy may not be feasible in high‐prevalence, low‐income settings.